Several Jensen–Grüss inequalities with applications in information theory - Butt, S. I.; Pečarić, Ð.; Pečarić, J.; Butt, S. I.; Pečarić, Ð.; Pečarić, J. (Institute of Mathematics, NAS of Ukraine, 2023)
UDC 517.5 Several integral Jensen–Grüss inequalities are proved together with their refinements. Some new bounds for integral Jensen–Chebyshev inequality are obtained. The multidimensional integral variants are also presented. In addition, some integral Jensen–Grüss inequalities for monotone and completely monotone functions are established. Finally, as an application, we present the refinements for Shannon's entropy.